An evaluation of the guidelines of the Society of Obstetricians and Gynaecologists of Canada. (3rd July 2016) - Ghui, Roslyn; Bansal, Jassimran Kaur; McLaughlin, Catarina; Kotaska, Andrew; Lokugamage, Amali
Abstract : Clinical practice guidelines hope to offer unbiased, evidence-based guidance for clinicians. This paper examines levels of evidence contained within the guidelines of the Society of Obstetricians and Gynaecologists of Canada and compares classification of the recommendation (CoR) A/B/C/D/E/L (derived from evidence and consensus) versus quality of evidence assessment (QoEA) I-III. 1250 recommendations were analysed and 43% of recommendations were graded as "good" evidence, the highest grade of CoR, while just 24.6% of recommendations were based on the highest level of QoEA (level I). The paper discusses possible reasons for this discrepancy. The authors hope that this analysis promotes greater transparency in evidence-based medicine ultimately leading to using the best quality of evidence available yet taking into account any areas of scientific uncertainty. This will enhance respectful care of patients, while taking into account their autonomy and furthering the cause of patient centre care.